Routine cranial CT before lumbar puncture in HIV positive adults presenting with seizures at Mitchells Plain Hospital in Cape Town - Moolla, Salma Abdulkadir (Department of Public Health and Family Medicine, 2015)
Current international guidelines recommend that a cranial computed tomography (CT) be performed, on all HIV positive patients presenting with new onset seizures, before a lumbar puncture (LP) is performed. In the South African setting, however, this delay could be life threatening. This study sought to measure the number of cranial CTs that contraindicate an LP and to predict which clinical signs and symptoms are likely to pose an increased risk from LP. Methods: The study was performed at a district level hospital in the Western Cape. Data was collected retrospectively from October 2013 to October 2014. Associations between categorical variables were analysed using Pearson's Chi-squared test. Generalised linear regression was used to estimate prevalence ratios. Results 100 out of 132 patients were studied. Brain shift contraindicated an LP in 5% of patients. Patients with brain shift presented with: decreased level of consciousness, focal signs, head ache and neck stiffness. 25% of patients had a space occupying lesion (defined as a discreet lesion that has a measurable volume) or cerebral oedema. Multivariate analysis showed a CD4 count < 50 (p=0.033) to be a statistically significant predictor of patients with a space occupying lesion (SOL) and cerebral oedema. Univariate analysis showed focal signs (p=0.0001), neck stiffness (p=0.05), vomiting (p=0.018) and a GCS<15 (0.002) to be predictors of SOL and cerebral oedema.